2016
DOI: 10.18632/oncotarget.8870
|View full text |Cite
|
Sign up to set email alerts
|

ZNF224, Krüppel like zinc finger protein, induces cell growth and apoptosis-resistance by down-regulation of p21 and p53 via miR-663a

Abstract: ZNF224 is a Krüppel-associated box-containing zinc-finger protein which represses gene transcription by interacting with various co-repressors. However, its consensus DNA sequences and target genes are not fully identified. In this study, we identified and characterized consensus DNA sequences containing 5′-CAGC-3′; recognized by ZNF224 through ChIP-sequencing, which further confirmed by ELISA, SPR, qPCR, and luciferase activity assay. ZNF224 increased miR-663a transcription by binding to miR-663a promoter, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…In addition, it is known that ZNF224 primarily localizes to the nucleus and forms a punctate pattern (12). Therefore, we hypothesized that the interaction between ZNF224 and MED28 may occur in the nucleus.…”
Section: Nucleus-specific Interactions Of Znf224 With Med28mentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, it is known that ZNF224 primarily localizes to the nucleus and forms a punctate pattern (12). Therefore, we hypothesized that the interaction between ZNF224 and MED28 may occur in the nucleus.…”
Section: Nucleus-specific Interactions Of Znf224 With Med28mentioning
confidence: 96%
“…In a previous study, it was found that ZNF224, a KRAP-ZFP, served a function as a transcriptional repressor upon DNA damage and that the overexpression of ZNF224 results in tumor formation (12). In addition, it was observed that ZNF224 was degraded in a time-dependent manner upon DNA damage (12). Previous studies have revealed that MEDs possess functions as co-repressors or co-activators of transcription in eukaryotic cells (14,22).…”
Section: Nucleus-specific Interactions Of Znf224 With Med28mentioning
confidence: 98%
See 3 more Smart Citations